Study on ultrasonic vibration assisted upsetting of 6063 aluminum alloy. (2017) - Xie, Zhendong; Guan, Yanjin; Zhai, Jiqiang; Zhu, Lihua; Zhong, Chongkai
Abstract: Ultrasonic vibration assisted metal forming is a novel kind of combined forming processes. 6063 aluminum alloy upsetting tests with and without ultrasonic vibration under different conditions were conducted. The effects of ultrasonic vibration on upsetting load, material flow stress, relative reduction in height, die/workpiece interface friction and microstructure, as well as the influence of height-diameter ratios on the ultrasonic vibration effect, were studied. After applying ultrasonic vibration, upsetting load, material flow stress and compressive strength decrease apparently, the relative reduction becomes larger than no ultrasonic vibration, and the frictional coefficient of the die/workpiece interface decreased significantly. Moreover, the surface hardness of the specimen improves slightly and increases with the increase of the amplitude and the ultrasonic vibration is helpful to the grain refinement and grain refinement efficiency of the upsetting.